2004
DOI: 10.1021/jm031127c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Quantitative Structure−Activity Relationship of Hydrazones ofN-Amino-N‘-hydroxyguanidine as Electron Acceptors for Xanthine Oxidase

Abstract: A series of new N-hydroxyguanidines were synthesized and tested for electron acceptor activity on bovine milk xanthine oxidase using xanthine as reducing substrate. Manual inspection of the structure-activity data revealed that molecules containing nitro groups ("set A") show a different structure-activity relationship pattern compared to non-nitro compounds ("set B"). Accordingly separate QSAR models were built and validated for the two sets. Substantial differences were found in properties governing acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…They reported that the results of the structure-based molecular modeling exhibited interactions between coumarins and the molybdopterin region of XO and that the carbonyl pointed toward the Arg880, and the ester O atom formed hydrogen bonds with Thr1010. Prusis et al [22] studied quantitative structure activity of hydrazones of N-amino-N 0 -hydroxyguanidine by measuring electron acceptor capacities for xanthine oxidase. They divided molecules into two groups one with nitro groups and the other without nitro groups based on the manual inspection of the structure-activity data.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the results of the structure-based molecular modeling exhibited interactions between coumarins and the molybdopterin region of XO and that the carbonyl pointed toward the Arg880, and the ester O atom formed hydrogen bonds with Thr1010. Prusis et al [22] studied quantitative structure activity of hydrazones of N-amino-N 0 -hydroxyguanidine by measuring electron acceptor capacities for xanthine oxidase. They divided molecules into two groups one with nitro groups and the other without nitro groups based on the manual inspection of the structure-activity data.…”
Section: Introductionmentioning
confidence: 99%
“…Our group synthesized and assayed the trypanocidal activities of 34 new megazol derivatives (7,8), exploring the hypothesis that the introduction of a radical scavenger arylhydrazone moiety in the heterocyclic framework of megazol could modulate the production of toxic nitro anion radical species, thus avoiding potentially mutagenic properties (22,31). The derivatives were designed by molecular hybridization between megazol and guanylhydrazones, compounds previously shown by one of the authors to display a strong activity against trypomastigote forms of T. cruzi (26).…”
mentioning
confidence: 99%
“…The molecular design explored the introduction of the pharmacophoric N-arylhydrazone subunit (A) from 8 ( Figure 9) to the nitroimidazole derivative (4), in order to act as a radical scavenger (Mahy et al, 1993;Prusis et al, 2004) that would abolish the oxidative stress that induces the formation of toxic species resulting from the formation of reactive nitroderivatives. Among a series of substituted arylhydrazone derivatives tested as trypanocidal agents, the catechol derivative called brazilizona A (9) ( Figure 9) showed remarkable activity (IC 50 = 5.3 M), being two fold more active than megazol (4) (IC 50 = 9.9 M) against blood trypomastigote forms of T. cruzi (Carvalho et al, 2004).…”
Section: Discovery Of Brazilizones a And Nmentioning
confidence: 99%